Pollinator foraging tactics have divergent consequences for the mating system of a tropical plant. Issue 3 (2nd December 2022) - Torres‐Vanegas, Felipe; Hadley, Adam S.; Kormann, Urs G.; Jones, Frank Andrew; Betts, Matthew G.; Wagner, Helene H.
Summary: Resolving the consequences of pollinator foraging behaviour for plant mating systems is a fundamental challenge in evolutionary ecology. Pollinators may adopt particular foraging tactics: complete trapline foraging (repeated movements along a fixed route), sample‐and‐shift trapline foraging (a variable route that incorporates information from previous experiences) and territorial foraging (stochastic movements within a restricted area). Studies that integrate these pollinator foraging tactics with plant mating systems are generally lacking. We investigate the consequences of particular pollinator foraging tactics for Heliconia tortuosa . We combine parentage and sibship inference analysis with simulation modelling to: estimate mating system parameters; infer the foraging tactic adopted by the pollinators; and quantify the impact of pollinator foraging tactics on mating system parameters. We found high outcrossing rates, ubiquitous multiple paternity and a pronounced departure from near‐neighbour mating. We also found that plants repeatedly receive pollen from a series of particular donors. We infer that the pollinators primarily adopt complete trapline foraging and occasionally engage in sample‐and‐shift trapline foraging. This enhances multiple paternity without a substantial increase in near‐neighbour mating. The particular pollinator foraging tactics have divergent consequences for multiple paternity and near‐neighbour mating. Thus, pollinator foraging behaviour is an important driver of the ecology and evolution of plant mating systems.